La evolución de los recursos cinematográficos - Carbonell i Saurí, Ricard (Cuadernos de Documentación Multimedia, 2009)
This paper “The Evolution of the Cinematographic Resources” is related to the Universidad Complutense de Madrid program “Teoría y Análisis y Documentación Cinematográfica” of Information Sciences. In order to its publication in Cuadernos de Documentación Multimedia, the introductory chapters of the investigation and the author conclusions have been included.